2015
DOI: 10.1093/inthealth/ihv052
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ear disease and hearing impairment on the lives of Nepali patients in Pokhara: a qualitative study

Abstract: This research suggests that a 'stigma cycle' has developed and that participants are being trapped within it. This impacts adversely upon individuals' personal, social and economic development, limiting the human capital available to Nepal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…A total of six studies reported mental health problems associated with bullying behaviors and two also reported physical health problems. 15,17,18,[23][24][25] Four studies collected quantitative data related to consequences of bullying. 15,17,18,23 Akram et al found that victimization predicted a significant proportion of physical and psychosocial problems.…”
Section: Health Consequences Of Bullying For Dhh Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of six studies reported mental health problems associated with bullying behaviors and two also reported physical health problems. 15,17,18,[23][24][25] Four studies collected quantitative data related to consequences of bullying. 15,17,18,23 Akram et al found that victimization predicted a significant proportion of physical and psychosocial problems.…”
Section: Health Consequences Of Bullying For Dhh Childrenmentioning
confidence: 99%
“…23 Two studies presented qualitative data regarding the consequences of bullying. 24,25 The interviews conducted by Skilton et al relayed themes of self-esteem issues, felt-stigma, and fears of maltreatment that prevented formation of new friendships following peer victimization. 24 Interviews conducted by Terkektsi et al reiterated themes of depression, self-esteem issues, and isolation in DHH children who were victims of bullying.…”
Section: Health Consequences Of Bullying For Dhh Childrenmentioning
confidence: 99%
“…The narratives of being teased about hearing and discharge, mixed reactions from the community and feelings of 'hurt and upset from the stigma' are common to both this study and the study by Skilton et al (2016). 9 However, Skilton et al reported that none of their participants 'recounted teachers displaying negative or stigmatising behaviour', whereas our participants gave mixed answers on this topic.…”
Section: Stigmamentioning
confidence: 50%
“…There is however a dearth of qualitative literature on the topic, and to our knowledge there has only been one such study previously conducted in Nepal. 9 Qualitative research is particularly useful for exploring QoL as it places emphasis on the experiences and views of the participants in a way that quantitative research cannot. 10 The Britain Nepal Otology Service has been providing a community-based ear programme in Western Nepal since 2006.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to experiencing stigma and discrimination, evidence suggests that children with unmanaged hearing loss have lower levels of literacy and poorer educational attainment compared to children with normal hearing [2,3,4,5]. This, in turn, can limit employment opportunities later in life and increase the risk of poverty [6,7].…”
Section: Introductionmentioning
confidence: 99%